2020
DOI: 10.3390/v13010002
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Epithelial Cells Respond to Lactobacillus plantarum but Provide No Cross-Protection against Virus-Induced Inflammation

Abstract: Virus-induced inflammation plays a critical role in determining the clinical outcome of an acute respiratory virus infection. We have shown previously that the administration of immunobiotic Lactobacillus plantarum (Lp) directly to the respiratory tract prevents lethal inflammatory responses to subsequent infection with a mouse respiratory virus pathogen. While Lp-mediated protective responses involve non-redundant contributions of both Toll-like receptor 2 (TLR2) and NOD2, the cellular basis of these findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
(152 reference statements)
0
6
0
Order By: Relevance
“…These contrasting results were also reported by Rosenberg and colleagues. The researchers demonstrated that the nasal priming of mice with the HK immunobiotic L. plantarum NCIMB 8826 provided protection against the lethal sequelae of PVM [ 14 , 15 , 16 ] and IFV [ 48 ] infections. The in vivo protective effects of the NCIMB 8826 strain were not related to the reduction in virus replication and clearance, but to efficient regulation of the inflammatory response that minimized the lung damage [ 15 , 16 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These contrasting results were also reported by Rosenberg and colleagues. The researchers demonstrated that the nasal priming of mice with the HK immunobiotic L. plantarum NCIMB 8826 provided protection against the lethal sequelae of PVM [ 14 , 15 , 16 ] and IFV [ 48 ] infections. The in vivo protective effects of the NCIMB 8826 strain were not related to the reduction in virus replication and clearance, but to efficient regulation of the inflammatory response that minimized the lung damage [ 15 , 16 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The researchers demonstrated that the nasal priming of mice with the HK immunobiotic L. plantarum NCIMB 8826 provided protection against the lethal sequelae of PVM [ 14 , 15 , 16 ] and IFV [ 48 ] infections. The in vivo protective effects of the NCIMB 8826 strain were not related to the reduction in virus replication and clearance, but to efficient regulation of the inflammatory response that minimized the lung damage [ 15 , 16 , 48 ]. Of note, studies in two cell culture models, MLE-12 cells (mouse lung type II alveolar epithelial like-cells) and mTECs cells (polarized mouse tracheal epithelial cells) revealed the inability of HK L. plantarum NCIMB 8826 to reduce the production of CCL2, CCL5, CXCL1, and CXCL10 induced by IFV infection, using a protocol that replicated experimental conditions that were effective in vivo [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were autoclaved at 121°C for 15 min. Then, L. reuteri and B. bifidum were heat inactivated at 70°C for 30 min, washed once in sterile, endotoxin‐free phosphate‐buffered saline (PBS), resuspended in PBS with 0.1% bovine serum albumin (BSA) (Gabryszewski et al, 2011; Mai et al, 2020) and stored at −20°C. The diluent was prepared in sterile, endotoxin‐free PBS (1 × 10 7 cells ml −1 ) before using L. reuteri and B. bifidum .…”
Section: Methodsmentioning
confidence: 99%
“…Relative expression of proinflammatory and immunomodulatory mediators in BAL fluid of mice inoculated with a lethal vs. sublethal dose of PVM (day 7) and mice inoculated with a sublethal dose of PVM alone (day 7 vs. day 21) was evaluated using the Proteome Profiler Array, Panel A and the Mouse Angiogenesis Profiler Array (both from R&D Systems, Minneapolis, MN, USA) as previously described [33]. Each profiler membrane was probed with 500 µL BAL fluid (100 µL from each of 5 mice per group).…”
Section: Profiling and Elisasmentioning
confidence: 99%